Analisis Kebutuhan Fisik dan Energi Atlet Pencak silat sebagai Dasar Pengembangan Model Latihan HIIT - nelson, sonya; Neldi, Hendri; Bahtra, Ridho (Jurnal Sporta Saintika, 2026)
Pencak silat is a martial art that demands a combination of physical ability, technique, and strategy. The intermittent, high-intensity nature of the competition means that athletes' energy needs are simultaneously dominated by the anaerobic and aerobic systems. Therefore, a training model capable of accommodating these physiological demands is needed, one of which is High-Intensity Interval Training (HIIT). This article aims to analyze the physical and energy needs of pencak silat athletes as a basis for developing an effective HIIT training model. The method used is a literature review of various studies related to sports physiology and martial arts athlete performance. The analysis results indicate that pencak silat athletes require anaerobic endurance, muscle strength, speed, agility, and good aerobic capacity. The HIIT model is considered relevant because it can increase VO₂max capacity, lactate tolerance, and energy efficiency. Thus, developing a HIIT program based on the specific needs of pencak silat can optimally improve athlete performance.